Effects of Influence of Audit Committee and Senior Managers over the Internal Auditors and Type of Internal Control Deficiency on Internal Auditors - Sajjad Naghdi; Elahe Salmanzadeh Aghdam; Javad Esmaeili; Vahid Ahmadian (پژوهش‌های تجربی حسابداری)
Internal auditors are a vital control element in modern organizations, with the internal audit function serving as a key tool for managers to evaluate internal controls and develop strategies to enhance performance. This study investigates the influence of management and audit committee dynamics, as well as the nature of internal control weaknesses, on internal auditors’ assessments of these weaknesses. The research employed an experimental method with a 2x2 between-subjects factorial design, manipulating two independent variables: the influence of the audit committee and management on internal audit performance, and the type of internal control weakness (pervasive or process-specific). The statistical sample consisted of 123 auditors from internal audit units of companies in 1403 (2024–2025), selected using convenience sampling. Data analysis and hypothesis testing were conducted using SPSS software, with variance analysis and mean comparison tests. The results indicate that internal auditors are more likely to classify process-specific control weaknesses as significant compared to pervasive control weaknesses. Additionally, consistent with motivational reasoning theory, neither audit committee nor management influence affects auditors’ evaluations of pervasive control weaknesses. Consequently, internal auditors may avoid reporting pervasive weaknesses to appease managers and the audit committee, despite these being effective controls.